Industry-level estimates of export quality accounting for global value chains - Konstantin M. Wacker; Xianjia Ye; Dea Tusha; Asia Celani (Scientific Data)
Abstract Offering high-quality versions of a product provides countries with a competitive advantage. Economic measures of countries’ export quality, however, neglect that exported goods depend on foreign parts and components supplied by other countries. We provide a novel industry-level dataset of export quality that takes such global input-output linkages into account. We therefore link conventional export quality measures to input-output tables. This allows us to project out the imported intermediate input quality from overall export quality. The constructed dataset covers 76 countries and 21 industries. Our novel measure is positively correlated with countries’ income per capita and with industries’ growth of value added. Our data can be used to better understand the role of export quality for industries’ international competitiveness, macroeconomic developments, and to investigate how global supply chains matter in this context – an issue that has become apparent through Covid, war-related sanctions, and recent geopolitical restructuring of global supply chains.